Comparison of Adiponectin Levels in Patients with Familial and Non-Familial Keloid History - Finarsih ES, Ella; Putra, Imam Budi; Wardani, Meidina Kesuma (Journal of Society Medicine, 2025)
Introduction: Keloid is an abnormal wound healing condition influenced by various factors, including adiponectin levels and genetic predisposition. The role of adiponectin in keloid formation, particularly concerning familial and non-familial history, remains unclear. This study aims to compare adiponectin levels in keloid patients with and without a familial history of keloid formation. To compare adiponectin levels in patients with familial and non-familial keloid history. Methods: This observational analytic study utilized a cross-sectional design involving 40 keloid patients. Participants underwent anamnesis, dermatological examination, and blood sampling to measure serum adiponectin levels using enzyme-linked immunosorbent assay (ELISA). Data were analyzed descriptively using IBM SPSS Statistics version 21. Results: Keloid was more frequently observed in female patients, particularly in the 18–25-year age group. The mean serum adiponectin level among all participants was 11.01±8.34 μg/ml. In patients with a familial history of keloid, 40.0% had low adiponectin levels, while 42.5% of those without a familial history also exhibited low levels. Statistical analysis revealed no significant difference in adiponectin levels between the two groups, suggesting that low adiponectin levels are a common feature in keloid patients regardless of genetic predisposition. Conclusion: Low adiponectin levels are prevalent among keloid patients, but they are not significantly associated with a familial history of keloid formation. Further research is needed to explore the mechanisms linking adiponectin to keloid development.